Analysis And Communication Strategy For Agro-Education Development Of Kandi Fruit Garden In Sawahlunto City - Fatmi Dona Aisyah*; Yenni Oktavia; Zul Irfan Irfan (Universitas Syiah Kuala, 2023)
This study aims to: (1) Analyze the communication process carried out by the manager in the development of Kandi Fruit Garden Agroedutourism; (2) Develop a communication strategy design in the development of Kandi Fruit Garden Agroedutourism. This research uses a constructivist paradigm with a qualitative approach. The mechanism for determining informants is Purposive sampling, where informants are determined based on their knowledge and involvement in the development of Agroeduwisata candi orchards. The result of this study is a Communication Strategy in the development of Kandi Fruit Garden Agroedutourism by utilizing Kandi Fruit Garden Agroedutourism Branding which comes from former mining land into productive fruit plants must be carried out on several social media and other promotional media so that it is easier to build a positive image of local and foreign tourists. Agroedutourism managers need cooperation with all levels of relevant stakeholders, to succeed in the development of sustainable agro-tourism with all its benefits in the future, it is necessary to improve the quality and quantity of human resources and institutions of Kandi Fruit Garden Agroedutourism managers so that they can innovate in facing the challenges of competition between tourist attractions.